Prioritization Of Research Under National Aids Control Programme In India Using Nominal Group Technique - Sogarwal, R; Bachani, D (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: During the fi rst 2 years of the fi ve year plan of India’s National AIDS Control Programme Phase-III (NACP-III; 2007-12), various interactive consultative workshops were organized in collaboration with development partners with the objective of identifying priority areas for operational research and further development of research protocols adopting mentorship approach. Methodology: This article is an attempt to present the Nominal Group Technique (NGT) which was used to identify a set of fundable and practically feasible research priorities under NACP-III specifi cally focusing on Prevention of Parent to Child Transmission (PPTCT) and Pediatric HIV Care in India. The activity was undertaken with support of UNICEF in the year 2010. A total of 110 persons participated in the consultation clustering into 37, 36 and 37 members in Group A, B and C, respectively. The participants refl ected the mix of policy makers / decision makers (8), programme managers (12), implementers (36), subject experts / researchers (28), other stakeholders (16). Results: A total of nine highest priority research questions were identifi ed by all the groups in the assigned themes. The value of Kendall’s W coeffi cient of concordance was 0.68, which shows signifi cant agreement among raters on priority research questions (chi-square=16.35; p=0.03). Conclusion: Based on our experience, we can conclude that NGT was found to be an important tool for setting research priorities that is more democratic and transparent than the traditional methods. By applying various stages of the group sessions, participants can experience the rethinking process with reference information to enhance their judgment. The results of our experience may help programme managers / policy makers to plan similar and more improved method in other element of NACP as well as other health programmes. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5888 SAARCTB 2011; 8(1): 20-30